Case report: Dupilumab: a promising treatment option for adult linear IgA bullous dermatosis with severe pruritus - Wang, Li; Peng, Jing; Chen, Jinbo (Frontiers in Immunology, 2024)
Linear IgA bullous dermatosis (LABD) is an acquired autoimmune subepidermal blistering disorder. Diagnosis always relies on skin pathology and direct immunofluorescence (DIF), with typical linear deposits of IgA along the basement membrane zone (BMZ). The typical clinical manifestation is tense bullae arranged like the “string of pearls” companied with severe pruritus. Dapsone is often considered first-line therapy for LABD, and it is necessary to test the HLA-B*1301 gene to prevent the occurrence of dapsone-induced hypersensitivity syndrome (DHS). Here we report a case of LABD resistant to corticosteroid and sulfasalazine, while waiting for HLA-B*1301 gene test results, dupilumab was used to control severe pruritus.